A multi-modal approach to functional neuroimaging - Brookes, Matthew Jon (2005)
The work undertaken involves the use of functional magnetic resonance imaging (fMRI) and magnetoencephalography (MEG) as separate but complementary non-invasive functional brain imaging modalities. The aim in combining fMRI and MEG is centred around exploitation of the high temporal resolution available in MEG, and the high spatial resolution available in fMRI. However, whilst MEG represents a direct measure of neuronal activity, BOLD fMRI is an indirect measure and this makes the two modalities truly complementary. In both cases, the imaging signals measured are relatively poorly understood and so the fundamental question asked here is: How are the neuromagnetic effects detectable using MEG related to the metabolic effects reflected in the fMRI BOLD response? Initially, a novel technique is introduced for the detection and spatial localisation of neuromagnetic effects in MEG. This technique, based on a beamforming approach to the MEG inverse problem, is shown to yield accurate results both in simulation and using experimental data. The technique introduced is applied to MEG data from a simple experiment involving stimulation of the visual cortex. A number of heterogeneous neuromagnetic effects are shown to be detectable, and furthermore, these effects are shown to be spatially and temporally correlated with the fMRI BOLD response. The limitations to comparing only two measures of brain activity are discussed, and the use of arterial spin labelling (ASL) to make quantitative measurements of physiological parameters supplementing these two initial metrics is introduced. Finally, a novel technique for accurate quantification of arterial cerebral blood volume using ASL is described and shown to produce accurate results. A concluding chapter then speculates on how these aCBV measurements might be combined with those from MEG in order to better understand the fMRI BOLD response.